The Effect Of Good Corporate Governance On Financial Performance With Intellectual Capital As A Moderator (An Empirical Study Of Banking Subsector Companies Listed On The Indonesia Stock Exchange From 2021 To 2024) - Bunga Maulidya Putri; Komala Ardiyani (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Financial performance is an indicator of a company’s ability to achieve its economic goals through efficient and sustainable management of assets, capital, and operational activities. This study aims to examine and analyse the influence of institutional ownership,board of directors, and board of commissioners on financial performance, and to examine the moderating effect of intellectual capital on the relationship between institutional ownership, board of directors, and board of commissioners on financial performance. The population in this study was banking subsector companies listed on the indonesia stock exchange in 2021-2024. Based on purposive sampling result, 36 companies were selected as samples that met the criteria. This study used Partial Least Squares (PLS)-Structural Equation Modeling (SEM) to test the hypotheses due to the non-normal distribution of data for several variables and the limited sample size. The results indicate that institutional ownership has a positive and significant effect on financial performance. board of directors has a positive and significant effect on financial performance. Board of commissioners has a positive and significant on financial performance. Intellectual capital reduces the positive effect of institutional ownership on financial performance. Intellectual capital does not moderate the effect board of directors on financial performance. Intellectual capital does not moderate the effect board of commissioners on financial performance.